2013
DOI: 10.1021/jo302455d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of O6 in Mannosylations Using Benzylidene Protected Donors: Stereoelectronic or Conformational Effects?

Abstract: The stereoselective synthesis of β-mannosides and the underlying reaction mechanism have been thoroughly studied, and especially the benzylidene-protected mannosides have gained a lot of attention since the corresponding mannosyl triflates often give excellent selectivity. The hypothesis for the enhanced stereoselectivity has been that the benzylidene locks the molecule in a less reactive conformation with the O6 trans to the ring oxygen (O5), which would stabilize the formed α-triflate and subsequent give β-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 86 publications
0
31
0
Order By: Relevance
“…This transforms all three donors into the corresponding anomeric triflates, 2124,48,60 prior to addition of the acceptor nucleophiles. The pre-activation set-up generates a pool of reactive intermediates in the absence of the acceptor, thereby eliminating product forming pathways that originate from direct displacement reactions on the activated parent donor species.…”
Section: Resultsmentioning
confidence: 99%
“…This transforms all three donors into the corresponding anomeric triflates, 2124,48,60 prior to addition of the acceptor nucleophiles. The pre-activation set-up generates a pool of reactive intermediates in the absence of the acceptor, thereby eliminating product forming pathways that originate from direct displacement reactions on the activated parent donor species.…”
Section: Resultsmentioning
confidence: 99%
“…It is unlikely that the lower selectivity observed for substrates with an oxygen atom at C-3 (leading to products 21 and 23 ) was caused by different energies associated with developing eclipsing interactions between the hydrogen atoms of C-2 and the substituent at C-3 (carbon vs. oxygen) upon addition. The barriers to rotation of methyl groups in the anti conformations of H 3 C–CH 2 CH 2 CH 3 and of H 3 C–CH 2 OCH 3 are quite similar (3.21 kcal/mol and 3.08 kcal/mol, respectively 22,23 ), and the difference in rotational barriers of cyclohexane(10.2 kcal/mol) 39 and tetrahydropyran (10.3 kcal/mol) 40 also compare well, so it should make little difference sterically what atom is at C-3 22 .…”
Section: Discussionmentioning
confidence: 98%
“…The conclusions of these studies can be used in a number of settings, including reactions of oxocarbenium ions with carbon and hydride nucleophiles 17 and nucleophilic additions to cyclic iminium ions 18,19 . The stereochemical model can be applied to the chemistry of carbohydrates 20 and nucleosides, 21 which required consideration of the influence of fused rings, which also control the reactions of six-membered-ring acetals 22,23 . For example, we demonstrated that rings fused to the five-membered ring at C-3 and C-4, 24 as long as they are large enough, exert little influence on the selectivity, as evidenced by the similarity of selectivity of substitution reactions that give rise to tetrahydrofurans 1 and 2 (Chart 1) 25 .…”
Section: Introductionmentioning
confidence: 99%
“…48 Pedersen and coworkers found a bicyclic 6-carbamannosyl donor to exhibit β-selectivity approaching that displayed by the now classical 4,6- O -benzylidene protected mannosyl donors, prompting them to suggest that the benzylidene effect is mainly torsional in origin and that the electronic component was previously overestimated. 49 However, it was subsequently pointed out by Crich and coworkers that the replacement of an acetal oxygen in an alkylidene protected 4,6-diol by a methylene group, as in the Pedersen model, or even more so by a methoxymethylene group (Fig. 6) introduces numerous new torsional interactions.…”
Section: Protecting Groups and Influence Of Conformation On Reactivitymentioning
confidence: 99%